Analisis Kemampuan Berpikir Komputasi Mahasiswa melalui Penggunaan Aplikasi Math Master - Qori Aulia Hafni Nasution; Yahfizham Yahfizham (Lembag, 2025)
This study aims to analyze the impact of using the Math Master application on students' computational thinking skills. Computational thinking includes algorithmic thinking, logic, and problem-solving—essential abilities in learning mathematics. This research employed a descriptive quantitative approach with a questionnaire consisting of 10 statements, involving 30 student respondents. The results indicate a strong and significant relationship between the use of Math Master and students' computational thinking abilities. With a coefficient of determination of 56%, the application contributes positively to enhancing students' problem-solving and logical thinking skills. Therefore, Math Master is considered an effective alternative learning medium to support mathematics instruction in higher education.